University students’ perception on the fast food industry service quality in Terengganu / Arma Mohd Faizal Abu Bakar…[et al.] - Abu Bakar, Arma Mohd Faizal; Anuar, Jazira; Mohd Alias, Mohd Azuan; Mohamad, Tajulurrus (Faculty of Hotel and Management, Universiti Teknologi MARA, Selangor, Kampus Puncak Alam Campus, 2017)
Foodservice business is one of the fastest growing segments of the hospitality industry. The same trend can be viewed in Terengganu where fast food restaurants or also known as quick service restaurants are popular among youth. This study investigates the perceptions of university students with regards to fast food restaurants service quality in Terengganu, given that university students are considered major customers of fast food industry. This study adopted quantitative method where survey was conducted through the distribution of 200 self-administered questionnaires. Samples were university students from three universities. Findings indicate that majority university students perceived fast food restaurants in Terengganu to be of a high quality. Their fast food restaurant choices were strongly influenced by the restaurant’s cleanliness, consistency of menu items and location. It is noteworthy to investigate the perceptions of university students on fast food restaurants as it provides the valuable insights for restaurateurs into the attributes that are essential to university students when selecting a fast food restaurant.